2016
DOI: 10.1007/s00705-016-2986-5
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of genotype G9 during a five-and-a-half-year period in Turkish children with rotavirus diarrhea

Abstract: This study was done to understand the dynamics of rotavirus genotype distribution in Turkish children. Samples were collected from January 2006 through August 2011 from children at a hospital in Ankara. Rotavirus was detected in 28 % (241/889) of the samples. Genotype G9P[8] was predominant (28 %), followed by G1P[8] (16.3 %) and G2P[8] (15.9 %). G9 was absent in the samples from 2006 and 2007 and then re-emerged in 2008 and increased gradually. Phylogenetic analysis showed that Turkish G9 rotaviruses of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The main identified G and P genotypes of RVA were G1 and P [8] and G1P [8] was the most prevalent genotype from 2009 to 2013, except for 2 months in 2014, when the dominant genotype was G9P[8]similar to Kunming, China, where from February 2015 to January 2016 G9P [8] strains accounted for 79.4% of all RVA strains [3]. The distribution of G9 strains has increased worldwide in recent years, including Uganda [23], Turkey [24] and Cambodia [25]. Hence, the trend of RVA genotype distribution in Chengdu was similar to national and global trends in that G9P [8] may be the next predominant strain after G1P [8].…”
Section: Discussionmentioning
confidence: 99%
“…The main identified G and P genotypes of RVA were G1 and P [8] and G1P [8] was the most prevalent genotype from 2009 to 2013, except for 2 months in 2014, when the dominant genotype was G9P[8]similar to Kunming, China, where from February 2015 to January 2016 G9P [8] strains accounted for 79.4% of all RVA strains [3]. The distribution of G9 strains has increased worldwide in recent years, including Uganda [23], Turkey [24] and Cambodia [25]. Hence, the trend of RVA genotype distribution in Chengdu was similar to national and global trends in that G9P [8] may be the next predominant strain after G1P [8].…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, acute gastroenteritis is a serious public health problem, affecting over 352 000 children younger than 5 years old annually (http://tsim.saglik.gov.tr/tsim). Recent studies have revealed that RVA is responsible for 6‐28% of cases of childhood gastroenteritis . Rotavirus infections in Turkey are most commonly observed between the beginning of September and the end of May, with the highest rates occurring in the first 4 months of the year .…”
Section: Introductionmentioning
confidence: 99%
“…More than one third of infections occur in children younger than 2 years of age, and rates of rotavirus positivity are similar between males and females . Genotyping studies from different provinces over various time periods have indicated that G1‐G4 and G9 are the five most common genotypes and that there is major variation in the frequency of each of these genotypes over time . Although rotavirus vaccination has not yet been included in a universal vaccination program in Turkey, both Rotarix [RV1] and RotaTeq [RV5] are available in Turkish markets, and families who want to vaccinate their children can easily find these vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First discovered in 1995, the G9 genotype occured all over the world and became the fifth most commonly detected human RV (10). Furthermore, G9 frequency has increased of late, and it is the predominant genotype found in recent studies conducted in Turkey (11,12). In Turkey, RV vaccination is currently not included in the national immunization program.…”
Section: Introductionmentioning
confidence: 99%